2015
DOI: 10.6004/jnccn.2015.0022
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Cancer, Version 3.2015

Abstract: The NCCN Guidelines for Kidney Cancer provide multidisciplinary recommendations for the clinical management of patients with clear cell and non-clear cell renal carcinoma. These NCCN Guidelines Insights highlight the recent updates/changes in these guidelines, and updates include axitinib as first-line treatment option for patients with clear cell renal carcinoma, new data to support pazopanib as subsequent therapy for patients with clear cell carcinoma after first-line treatment with another tyrosine kinase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
118
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 206 publications
(122 citation statements)
references
References 12 publications
2
118
0
2
Order By: Relevance
“…[9][10][11] In the United States, pazopanib (VOTRIENT, GlaxoSmithKline) 12 and sunitinib (SUTENT, Pfizer) 13 are approved by the U.S. Food and Drug Administration and are among the choices for first-line treatment of advanced RCC based on demonstrated improvement in progression-free survival (PFS). 14 Pazopanib is an oral, once-daily therapy and was approved in 2009. 12 The efficacy and safety of pazopanib has been demonstrated in a randomized, double-blind, placebo-controlled, phase III trial.…”
Section: Study Sample Selectionmentioning
confidence: 99%
“…[9][10][11] In the United States, pazopanib (VOTRIENT, GlaxoSmithKline) 12 and sunitinib (SUTENT, Pfizer) 13 are approved by the U.S. Food and Drug Administration and are among the choices for first-line treatment of advanced RCC based on demonstrated improvement in progression-free survival (PFS). 14 Pazopanib is an oral, once-daily therapy and was approved in 2009. 12 The efficacy and safety of pazopanib has been demonstrated in a randomized, double-blind, placebo-controlled, phase III trial.…”
Section: Study Sample Selectionmentioning
confidence: 99%
“…Based largely on such clinical trial evidence, NCCN guidelines recommend the use of everolimus and axitinib after failure with first TKI with category 1 recommendation. 17 Although head-to-head randomized comparisons are not available for all pairs of second targeted therapies, indirect comparisons of trial data have shown similar effectiveness for everolimus and axitinib. 28 In addition, in the case of the mTOR inhibitors everolimus and temsirolimus, a MOA different from that of a previous TKI also played a considerable role in treatment decisions.…”
Section: Discussionmentioning
confidence: 99%
“…10,16 Current NCCN guidelines recommend the use of VEGFR TKIs as first targeted therapy in patients with good-to-intermediate prognosis and the use of temsirolimus in patients with poor prognosis. 16,17 After failure of a first TKI, NCCN guidelines recommend using either another TKI, such as axitinib, or switching to a different MOA with everolimus. [16][17][18] Phase III trials, such as the AXIS trial comparing axitinib with sorafenib 15 and the RECORD-1 trial comparing everolimus with a placebo, have shown the efficacy of these treatments as second targeted therapies.…”
mentioning
confidence: 99%
“…Bu tümörlerin %90'ı histopatolojik olarak berrak hücreli tiptir ve en sık akciğerlere metastaz yaptıkları bildirilmiştir (4). Güncel rehberlerde, şüpheli böbrek kitlesi saptanan hastalarda, öncelikle akciğer grafisi, metastaz açısından şüpheli bir bulgu saptanması halinde ise bilgisayarlı tomografi ile toraks görüntülemesi yapılması önerilmektedir (5,6). Bunun yanı sıra, küçük böbrek kitlelerinde metastatik potansiyelin düşük olması ve bundan dolayı hastalarda tanıya yönelik ileri toraks görüntülemesinin ve girişimlerinin gereksiz olabileceği bildirilmiştir (7).…”
Section: Introductionunclassified